A Curious Greed - Free, Ian Laing (Auckland University of Technology, 2014)
This volume contains an Exegesis and a Creative Thesis, in this order. The Exegesis is an academic essay on the process used to produce the Thesis, which is a memoir. The memoir had its origin in a desire to explore the question of whether the author was in any way responsible for my wife becoming an alcoholic, a condition in which she died. We met in Sweden where she was born, became engaged there and were married six months later in Hamilton, New Zealand. Her name was Gerd, which is pronounced with a soft G like a Y and rhymes with Scottish laird. We had two sons, we visited Sweden five times (as often as we could afford) and lived for four years in Melbourne, Australia. We were together for fifty years. Why did it have to end so abruptly? We were very compatible. Our outlooks on existing things and our approaches to new things were remarkably similar. I admired her intelligence as well as her beauty, her passionate sense of social justice, her feeling for style, her robust sense of humour and her readiness for physical adventure. We communicated well in both English and Swedish. These matters are described in the memoir. The memoir examines whether my basic personality was defective in some way, enough to make her disappointed in me. I examine some of the events of my youth and adolescence that formed my character. Or was it perhaps the undoubted culture shock of moving from the advanced welfare state of Sweden in the 1950s, with its emphasis on equality for men and women and its tolerance of individual differences, to small-town New Zealand where difference was frowned upon? She undoubtedly paid a big personal price in living here, though she was quick to praise and ready to support the virtues of Aotearoa. Did she feel at the end of her life that she had made a mistake in coming here and marrying me? On the evidence I searched to find, I do not think so. The authorities referred to in the Exegesis assisted my search immeasurably. So what went wrong for Gerd? The conclusions I came to include a ‘Not Guilty’ verdict on the charge that I was responsible for her alcoholism, but I have to accept, I believe, a label of ‘involuntary assistant’ in the way she lived the last few years of her life. Our social drinking paved the way for her alcoholism. I conclude that other factors were also at work and I describe in the memoir the tragedy of her early dementia. I am left with an enormous gratitude that I shared a long period of time with a remarkable person. Her richness informs me still. *****
Keywords: Memoir; Exegesis